Post-HTS case report and structural alert: Promiscuous 4-aroyl-1, 5-disubstituted-3-hydroxy-2H-pyrrol-2-one actives verified by ALARM NMR. Issue 21 (1st November 2015) - Dahlin, Jayme L.; Nissink, J. Willem M.; Francis, Subhashree; Strasser, Jessica M.; John, Kristen; Zhang, Zhiguo; Walters, Michael A.
Graphical abstract